(untitled) (Pravaha, 2025)
Background: In developing countries like Nepal, payment from pocket for health facilities is a prime challenge. This leads to financial hardship and sometimes makes delay in treatment, particularly for poor people. To overcome these problems, the Government of Nepal introduced the Social Health Insurance program. The objective of this program is to provide financial protection and ensure equal access to quality health treatment. Objectives: The study aimed to explore the factors associated with community perception towards social health insurance in Sundarharaicha Municipality, Morang, Nepal. Material and Methods: The study used a cross-sectional study design. Using a structured questionnaire, primary data was gathered from 392 households of three wards randomly selected from Sundarharaicha Municipality, Morang. Descriptive analysis, chi-square tests, log normal regression were used to explore relationships among perception status, and socio-demographic variables. Cronbach’s alpha was used to measure Internal consistency of the perception. Results: The overall mean perception score towards SHI was 2.30 which was below the neutral midpoint of 3 on a five point Likert scale, indicating an unfavorable perception. Most respondents were disagreed that SHI was a worthwhile investment while only two respondents were strongly agreed. Cronbach’s alpha (0.92) confirmed the internal consistency of the perception scale. Mann-Whiteny test showed significant differences in perception scores across awareness status, gender, marital status, family type, ethnicity, religion, education status, and history of chronic disease of the household head (p < 0.10). Perception status was found significantly associated with ward of residence, gender, marital status, family type, source of information, and awareness status from bivariate analysis. A log normal regression revealed that ward of residence, awareness status, and source of knowing SHI were significant determinants of perception. Respondents residing in Ward no. 4 and Ward no. 8 had higher perception compared to those from the Ward no. 9. In contrast, respondents with high awareness status and those informed from health personnel, media, and relatives/friends had lower perception compared to those who had not heard about the program. Conclusion: This study assesses the perception of respondents towards SHI. The perception score was found to differ significantly across the categories of awareness, gender, marital status, family type, ethnicity, religion, education, and history of chronic disease of the household head. A log normal regression analysis identified ward of residence, awareness status, and source of information as the significant determinants of perception.